Soil health metrics for assessment of floodplain restorations - Joseph George Galella; Md Moklesur Rahman; Eric Moore; Marc Peipoch; Jinjun Kan; Alexis M Yaculak; Matthew Sena; Bisesh Joshi; Sujay S Kaushal; Shreeram Inamdar (Environmental Research Letters, 2025)
While healthy soils are critical for stream and floodplain restoration, little guidance is available to restoration practitioners on which soil metrics to measure and when to expect the signs of recovery post-restoration. Here, we address this important knowledge gap through a study of 37 soil metrics for 11 restored floodplains and two reference sites across a chronosequence of 0–22 years. Soil metrics differed in their sensitivity and response to restoration and followed different rates of change including fast (0–2 years), moderate (2–10 years), and slow (>10 years). Physicochemical metrics dominated the first two trajectories, whereas biological metrics, while sensitive, fell into the last trajectory. Soil recovery rates for restored sites differed considerably for reference sites highlighting the need to better define reference conditions. Availability of consistent and sensitive soil health metrics will allow restoration practitioners to better assess restoration recovery and receive regulatory credits for meeting restoration targets.